Komparasi Eksistensialisme Dan Humanisme Dalam Perspektif Pendidikan Islam - Khofifah Indar Parawansah (4, 2026)
This article examines the comparative differences between Existentialism and Humanism and their relevance from an Islamic educational perspective. Existentialism is understood as a school of thought that emphasizes individual freedom, self-awareness, and personal responsibility in determining the meaning of life. Meanwhile, humanism places humans at the center of development, with a focus on self-potential, psychological needs, and respect for human dignity. This study aims to identify the similarities and differences between the two schools of thought, while also examining how Islamic education can synthesize the positive values ​​of both within the framework of monotheism, morality, and the development of human nature. The method used is library research, which examines various relevant literature, including books, scientific journals, and academic works that discuss existentialism, humanism, and the principles of Islamic education. The analysis is conducted descriptively and comparatively to describe the characteristics of each school of thought, followed by a normative approach to examine its position from an Islamic educational perspective. The results of the study indicate that Islamic education can accommodate the values ​​of conscious and responsible freedom from existentialism, as well as the principles of potential development and respect for human dignity from humanism. This integration is reflected in learning practices such as deliberation, dialogic learning, and providing space for students to develop their potential. However, the entire process remains directed toward the formation of spiritual and moral values, thus producing individuals with a balance between intellectual, social, and religious aspects. Abstrak Artikel ini mengkaji komparasi antara Eksistensialisme dan Humanisme serta relevansinya dalam perspektif Pendidikan Islam. Eksistensialisme dipahami sebagai aliran yang menekankan kebebasan individu, kesadaran diri, serta tanggung jawab personal dalam menentukan makna hidup. Sementara itu, humanisme menempatkan manusia sebagai pusat pengembangan, dengan fokus pada potensi diri, kebutuhan psikologis, dan penghargaan terhadap martabat kemanusiaan. Penelitian ini bertujuan untuk mengidentifikasi persamaan dan perbedaan kedua aliran tersebut, sekaligus menelaah bagaimana pendidikan Islam mampu menyintesiskan nilai-nilai positif dari keduanya dalam kerangka tauhid, akhlak, dan pengembangan fitrah manusia. Metode yang digunakan adalah studi pustaka (library research) dengan menelaah berbagai literatur yang relevan, baik berupa buku, jurnal ilmiah, maupun karya akademik yang membahas eksistensialisme, humanisme, dan prinsip-prinsip pendidikan Islam. Analisis dilakukan secara deskriptif-komparatif untuk menggambarkan karakteristik masing-masing aliran, kemudian dilanjutkan dengan pendekatan normatif untuk melihat posisinya dalam perspektif pendidikan Islam. Hasil kajian menunjukkan bahwa pendidikan Islam dapat mengakomodasi nilai kebebasan yang sadar dan bertanggung jawab dari eksistensialisme, serta prinsip pengembangan potensi dan penghargaan terhadap martabat manusia dari humanisme. Integrasi ini tercermin dalam praktik pembelajaran seperti musyawarah, pembelajaran dialogis, serta pemberian ruang bagi peserta didik untuk mengembangkan potensinya. Namun, seluruh proses tersebut tetap diarahkan pada pembentukan nilai spiritual dan moral, sehingga menghasilkan individu yang seimbang antara intelektual, sosial, dan keagamaan.